Investigation of the Corrosion Process by X-Ray Phase Analysis - Ruzieva M; Vapoev H.M; Razzakov H.K; Nazarov S.I; Kodirov S.M. (Zien Journals, 2023)
This article presents an assessment of corrosion processes by X-ray phase analysis and the inhibitory ability of inhibitors using powder diffractometry (X-ray phase analysis) and scanning electron microscopy.
Keywords: Goethite; hematite; magnetite; solution